2012
DOI: 10.1890/es12-00122.1
|View full text |Cite
|
Sign up to set email alerts
|

Strontium isotopes in tap water from the coterminous USA

Abstract: Abstract. Strontium isotope analysis has proven useful in geo-location investigations of organic and inorganic materials and may complement the region-of-origin information provided by hydrogen and oxygen stable isotope analysis. In this study, we analyzed 99 drinking (tap) water samples collected from 95 municipal water systems across the USA to investigate the potential that 87

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 53 publications
1
44
1
1
Order By: Relevance
“…41 The results from the TVA spill confirmed that boron can be a sensitive indicator for metals leaching from CCRs, with boron content up to 1600 μg/L in downstream porewater in ash covered sediments, relative to the upstream and uncontaminated river water with boron of 6−9 μg/L (Figure 2). 9,29 Results from surface water at a site covered with spilled ash and limited water exchange (known henceforth as the Cove) 9,29 yielded low δ Sr variations in watersheds in the US 42,43 show that most of the southeastern, south, and central watersheds in the coterminous U.S. have a similar isotopic range that would mask the difference between CCR-impacted and naturally occurring background waters. Yet in other areas of the northeastern, northern, and western U.S., the isotopic ratios are either higher (e.g., northeastern U.S., Minnesota, southern Appalachian range) or lower (e.g., Southern Texas, Oregon) that would allow a clear distinction between CCRimpacted water and natural background.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…41 The results from the TVA spill confirmed that boron can be a sensitive indicator for metals leaching from CCRs, with boron content up to 1600 μg/L in downstream porewater in ash covered sediments, relative to the upstream and uncontaminated river water with boron of 6−9 μg/L (Figure 2). 9,29 Results from surface water at a site covered with spilled ash and limited water exchange (known henceforth as the Cove) 9,29 yielded low δ Sr variations in watersheds in the US 42,43 show that most of the southeastern, south, and central watersheds in the coterminous U.S. have a similar isotopic range that would mask the difference between CCR-impacted and naturally occurring background waters. Yet in other areas of the northeastern, northern, and western U.S., the isotopic ratios are either higher (e.g., northeastern U.S., Minnesota, southern Appalachian range) or lower (e.g., Southern Texas, Oregon) that would allow a clear distinction between CCRimpacted water and natural background.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10][11][12][13] Moreover, emerging applications for stable isotope fractionation of metals, such as Ca, in medicine are poised to dramatically alter the eld. [3][4][5][6][7][8][9][10][11][12][13] Moreover, emerging applications for stable isotope fractionation of metals, such as Ca, in medicine are poised to dramatically alter the eld.…”
Section: Introductionmentioning
confidence: 99%
“…There are two general baseline-development approaches in use: i) detailed sampling campaigns aimed at characterizing all potential sources of Sr (Hodell et al, 2004;Barnett-Johnson et al, 2008;Walther et al, 2008;Frei and Frei, 2011;Chesson et al, 2012;Muhlfeld et al, 2012) and ii) modeling approaches (Beard and Johnson, 2000;Bataille and Bowen, 2012;Bataille et al, 2013). Large-scale sampling campaigns are expensive and inherently incomplete, especially in vast remote regions, such as Alaska (AK), USA.…”
Section: Introductionmentioning
confidence: 99%